Revascularization Versus Medical Therapy in Patients Aged 80 Years and Older with Acute Myocardial Infarction. Issue 11 (12th August 2020) - Phan, Derek Q.; Rostomian, Ara H.; Schweis, Franz; Chung, Joanie; Lin, Bryan; Zadegan, Ray; Lee, Ming‐Sum
Abstract : BACKGROUND/OBJECTIVES: Older patients are underrepresented in acute coronary syndrome clinical trials. We sought to evaluate the benefits of revascularization in patients aged 80 years and older presenting with acute myocardial infarction (AMI). DESIGN: Retrospective study utilizing inverse probability of treatment weighting (IPTW). SETTING: Single tertiary referral center for an integrated healthcare system in southern California. PARTICIPANTS: Patients undergoing invasive coronary angiography for AMI between 2009 and 2019, and subsequently treated with percutaneous coronary intervention (PCI), coronary artery bypass grafting (CABG), or medical therapy alone. MEASUREMENTS: All‐cause mortality, nonfatal myocardial infarction (MI), and repeated revascularization. RESULTS: A total of 1, 433 patients aged 80 years or older (median age = 83.5 years; 66% male) presenting with AMI who underwent treatment with PCI (50%), CABG (12%), or medical therapy alone (38%) were included. Those treated with medical therapy were more likely to be Black, had one or more chronic total occlusions in any vessel, had more comorbidities, and had lower left ventricular ejection fraction. Baseline characteristics were well balanced after IPTW adjustment. Median follow‐up was 2.6 years. Revascularization (PCI or CABG) was associated with reduced mortality (hazard ratio (HR) = 0.66; 95% confidence interval (CI) = 0.60–0.73) and nonfatal MI (HR = 0.68; 95% CI = 0.58–0.78), but an increased need for repeated revascularization (HR = 1.60; 95% CI = 1.15–2.23). Separately comparing PCI or CABG alone versus medical therapy yielded similar results. Revascularization was associated with lower mortality in all subgroups, except in Black patients and those with prior CABG. CONCLUSION: Revascularization is superior to medical therapy in reducing all‐cause mortality and nonfatal MI in patients aged 80 years and older with AMI. Age alone should not preclude patients from potentially beneficial invasive therapies.